2018
DOI: 10.1016/j.drugalcdep.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

The importance of considering polysubstance use: lessons from cocaine research

Abstract: Based on the prevalence and known consequences of PSU, consideration of PSU in both human and animal research is vital for understanding patterns of substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 94 publications
4
74
0
2
Order By: Relevance
“…However, such cocaine and ceftriaxone-induced effects identified in rodents may not translate into the clinic, as 50–90% of cocaine users also use alcohol ( Grant and Harford, 1990 ; Rounsaville et al, 1991 ; Anthony et al, 1994 ; Brookoff et al, 1996 ; Kedia et al, 2007 ; Liu et al, 2018 ). Alcohol consumption in outbred Sprague-Dawley rats leads to increased NA core basal glutamate levels during early abstinence, with no changes in GLT-1 and xCT expression, and ceftriaxone is ineffective at changing GLT-1 expression after alcohol ( Pati et al, 2016 ; Stennett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, such cocaine and ceftriaxone-induced effects identified in rodents may not translate into the clinic, as 50–90% of cocaine users also use alcohol ( Grant and Harford, 1990 ; Rounsaville et al, 1991 ; Anthony et al, 1994 ; Brookoff et al, 1996 ; Kedia et al, 2007 ; Liu et al, 2018 ). Alcohol consumption in outbred Sprague-Dawley rats leads to increased NA core basal glutamate levels during early abstinence, with no changes in GLT-1 and xCT expression, and ceftriaxone is ineffective at changing GLT-1 expression after alcohol ( Pati et al, 2016 ; Stennett et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that cocaine users concurrently use other substances frequently, including alcohol ( Blow et al, 2011 ; Borders & Booth, 2013 ; Evans-Polce, Lanza, & Maggs, 2016 ; Hedden, Malcolm, & Latimer, 2009 ; Liu, Williamson, Setlow, Cottler, & Knackstedt, 2018 ), tobacco ( Winhusen et al, 2013 ), marijuana ( Gonçalves & Nappo, 2015 ; Liu et al, 2018 ), heroin ( Leeman, Sun, Bogart, Beseler, & Sofuoglu, 2016 ; Ojha, Sigdel, Meyer-Thompson, Oechsler, & Verthein, 2014 ; Oviedo-Joekes et al, 2015 ), and prescription medications ( Al-Tayyib, Rice, Rhoades, & Riggs, 2014 ; Chen et al, 2014 ; Evans-Polce et al, 2016 ; Herman-Stahl, Krebs, Kroutil, & Heller, 2006 ; Winhusen et al, 2013 ). Polysubstance users have been found to have a higher risk of overdose, emergency department (ED) visits, violence, accidental injury ( Macdonald et al, 2014 ), traffic accidents ( De Boni et al, 2014 ), and lower addiction treatment effectiveness ( Evans et al, 2015 ; Hou, Zhan, Zheng, Zhan, & Zheng, 2014 ; Liu et al, 2018 ) compared to mono-substance users. Polysubstance use has also been associated with worse physical health ( Quek et al, 2013 ; White et al, 2013 ), lower quality of life ( Kelly et al, 2017 ) and higher rates of mental health conditions, such as anxiety, depression, social phobia, and personality disorders ( Agrawal, Lynskey, Madden, Bucholz, & Heath, 2007 ; Chen et al, 2014 ; Evans et al, 2015 ; Kelly et al, 2017 ; Leeman et al, 2016 ; Quek et al, 2013 ; White et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in substance-using populations, polydrug use is common [23]. Considerations of drug-drug interactions with SCs are important clinically [24], but possible or unexpected biotransformation due to co-ingested compounds should also be considered.…”
Section: Introductionmentioning
confidence: 99%